2016
DOI: 10.1002/cm.21348
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of de novo centriole assembly in heat‐shocked mammalian cells

Abstract: Mammalian cells are capable of de novo centriole formation after the removal of existing centrioles. This suggests that de novo centriole assembly is repressed in normally duplicating cells to maintain a constant number of centrioles in the cells. However, neither the mechanism of de novo centriole assembly nor that of its hypothesized repression is understood due to the lack of an experimental system. We found that the heat shock (HS; 42°C, 2 h) of mouse embryonic fibroblasts caused the separation of centriol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Heat stress can induce both structural and numerical aberrations of centrosomes in human cancer cells [15,17,20]. In our experiments, we first found that heat stress alters centrosome organization.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Heat stress can induce both structural and numerical aberrations of centrosomes in human cancer cells [15,17,20]. In our experiments, we first found that heat stress alters centrosome organization.…”
Section: Resultsmentioning
confidence: 77%
“…Heat stress is another kind of mechanical factor that can induce multipolar cell divisions [14,15,16,17,18,19,20]. For example, by immunofluorescence assay, Nakahata [17] et al demonstrated the percentage of metaphases with multiple spindles of MCF-7 cells with about 3% in control and 71.0% in heat-shocked group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations